The Interplay of Financing Structures and Profitability in Islamic Banking: Does Asset Quality Moderate the Outcome? - Budi Kolistiawan (Business and Applied Management Journal, 2025)
This study examines the effects of debt, equity, and lease financing, as well as the financing-to-deposit ratio (FDR), on return on equity (ROE), with non-performing financing (NPF) as a moderating variable in Islamic banking. The research fills a gap in previous studies that reported inconsistent findings regarding the impact of Islamic financing structures on profitability. A quantitative, associative research design with a time-series approach is employed, using 52 quarterly observations from 2011 to 2023 sourced from BCA Syariah financial reports and the Financial Services Authority (OJK). Data are analyzed through Moderated Regression Analysis (MRA) to assess both direct and moderating effects. The results indicate that debt financing negatively and significantly affects ROE, while equity financing has a positive and significant impact. Lease financing and FDR show no significant effect on ROE. NPF significantly influences ROE and moderates the relationship between FDR and ROE, but does not moderate the relationships with other financing variables. These findings provide empirical evidence on the role of financing risk in shaping profitability in Islamic banks, offering practical insights for bank managers and regulators in optimizing financing strategies while mitigating risk to enhance financial performance.